Assessment of the Auchenorrhyncha Fauna of Winter Oilseed Rape Stands in Connection with the Disease Caused by Aster Yellows Phytoplasma - Kutas, János (GEORGIKON FOR AGRICULTURE, 2024)
The highly polyphagous aster yellows phytoplasma can infect winter oilseed rape as well. In Hungary, the first detection of the aster yellows phytoplasma in oilseed rape was reported in 2020. Leafhoppers are mentioned as the primary vectors of the pathogen, but only a few experiments have proven their transmission ability in Europe. In recent years, we aimed to survey the Auchenorrhyncha fauna of winter oilseed rape. Yellow sticky traps were primarily used to monitor insect populations, but sweep netting was also carried out. Zyginidia and Empoasca genera were the most abundant, but specimens of potentially aster yellows phytoplasma vectors such as Macrosteles and Psammotettix genera were also caught.
Keywords: winter oilseed rape; leafhoppers; aster yellows phytoplasma